Distance, Trade and FDI: A Hausman-Taylor SUR Approach - Peter Egger; Michael Pfaffermayr (Austrian Institute of Economic Research (WIFO), 2001)
This paper analyzes the effects of distance as a common determinant of exports and FDI in a three factors New Trade Theory model assuming that distance affects both pure trade costs and plant set-up costs. Exports and FDI are not necessarily substitutes with respect to distance since the predicted sign depends on its importance for fixed plant set-up costs relative to transportation costs. For the empirical specification, we suggest that the impact of of time-invariant variables such as distance is most appropriately analyzed in a Hausman-Taylor SUR model. In our application, outward FDI is negatively affected by distance while its effect on exports is insignificant. Exports and outward FDI are complementary with respect to the time-invariant unobserved factors and also with respect to the majority of the exogenous observed determinants.
Keywords: C33; F12; F23; 330; Multinationals; New trade theory; Panel econometrics; Neue Außenhandelstheorie; Multinationales Unternehmen; Auslandsinvestition; Theorie